WHEN LEADERSHIP TURNS TOXIC: BULLYING IN MALAYSIAN HIGHER EDUCATION INSTITUTIONS - Kuek, Thiam Yong; Choong, Yuen Onn; Awee, Azeyan; Mohsin, Farhana Hanim; Chai, Bobby Boon Hui; Yap, Timothy Tzen Vun (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
This study develops a conceptual model to explain workplace bullying among academics in Malaysian universities as an organisational phenomenon shaped by leadership and climate. Grounded in Conservation of Resources theory, the manuscript proposes that toxic leadership acts as an upstream source of resource depletion that increases vulnerability to repeated negative acts at work. Psychosocial safety climate (PSC) is positioned as a mediating mechanism that explains how leadership-related resource loss is translated into workplace bullying. Addressing gaps in Malaysian higher education research, the study advances two propositions: that toxic leadership positively affects workplace bullying, and that this relationship is transmitted indirectly through PSC. Methodologically, the study proposes a quantitative design using survey data from academics in Malaysian universities and structural equation modelling to test the hypothesised relationships. This study contributes to bullying and higher education literature by shifting attention from individual coping to systemic prevention, highlighting leadership practices and PSC as key organisational levers for healthier academic workplaces.